If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -8 = 10 + 3 Reorder the terms: -8 + 3b = 10 + 3 Combine like terms: 10 + 3 = 13 -8 + 3b = 13 Solving -8 + 3b = 13 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 3b = 13 + 8 Combine like terms: -8 + 8 = 0 0 + 3b = 13 + 8 3b = 13 + 8 Combine like terms: 13 + 8 = 21 3b = 21 Divide each side by '3'. b = 7 Simplifying b = 7
| 1.012x+3.25(x+1)-3=4.261 | | 214=1/3v | | 2z-z=77-71 | | 38.25=4.25h | | 0.129-5.38(0.772x+3)=0.6619 | | 3b=2x+5y | | -3+8-6= | | 8-y(y)=14 | | 7(-2x+7)+9=6(5x-5) | | 12n^3-5n^2-2n=0 | | 11b+9b=20b | | 8(2x-1)=-12 | | 8a+9a=17a | | x-4=12/7 | | 10y+2X=18 | | Y=2E-05(0.0058)-0.0006 | | 0.0058=2E-05x-0.0006 | | m-6=47 | | =0.0058 | | 3(3x-4)=7 | | p+11=96 | | 150+75d=75+100d | | 12n-(n-3)= | | 20+4.50h=9+5.75h | | -4(-14)= | | 1/-3*2y | | m-6=52 | | 8=2y-6/-3 | | Y=-x^2-2x-1-2 | | Y=-x^2-2x+1-2 | | 6-3(2)^3/(-8) | | -7x+15x-40x= |